Evaluation of Pharmaceutical Services at Pharmacy X Based on the Regulation of the Minister of Health Number 73 of 2016 - Tangkas, Hansel Hens; Normaidah, Normaidah; Mulia, Mulia; Asa, Raudatul Jannah; Melindawati, Vina (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
Pharmaceutical services are crucial in enhancing individuals' quality of life. Pharmacies must adhere to and apply the standard pharmaceutical services outlined in the Minister of Health Regulation Number 73 of 2016. Standard Pharmaceutical services still cannot be implemented perfectly in society, which impacts people's quality of life. This research provides relevant information for policy-making in the health sector and encourages the improvement of the quality of pharmaceutical services in the future. Pharmacy X has been established for 13 years and is in the middle of the market. Pharmacy X is also close to the Kapuas River. Both factors make Pharmacy X easily accessible to the community. This study aims to evaluate pharmaceutical services at Pharmacy X, Kapuas City. The method used in this research was qualitative, with direct observation and interview. This method was used to obtain results regarding the evaluation of pharmaceutical services. The results showed that Pharmacy X had already implemented standard pharmaceutical services. Nonetheless, it would be better if Pharmacy X had a counseling room that was large enough. Pharmacy X has played a role in enhancing the safety and efficacy of drug therapy for patients. In the future, enhancing technology-driven services and improving community access may serve as a priority to elevate the standard of pharmaceutical services. The professional practice of pharmacists in Indonesia is necessary to protect patients from inappropriate services. If pharmaceutical service standards are not implemented properly, there is a risk of endangering patient safety and increasing inequalities in access to health services.